Identifying factors that influence the patronage intention of Muslims and nonmuslims in Malaysia at Kopitiam: An extension of theory of planned behaviour - Koh, Yong Sieng (Universiti Malaysia Sarawak, (UNIMAS), 2013)
(The booming of Halal market, which is due to the growmg numbers of Muslims' population, has made the Halal marketplace too lucrative that the foods and beverages service providers cannot ignore. Specifically, we can see the booming market of modem Halal Kopitiams, which are owned by diverse ethnics of Malaysian and Non-Malaysian, to target on Non-Muslims and Muslims in Malaysia. As a result, eating and hangout at modem Halal Kopitiams has become a life culture in today's society. Unfortunately, there were some troublesome incidents happened recently like the misuse ofHalal Certificate and logo from the Kopitiams' owners to give the signal to the Muslim's customers that the operated Kopitiam is a modem Halal Kopitiam. Indeed, some of the owners even did not comply the Halal food standard, reducing the trust from Muslims toward the modem Halal Kopitiany Consequently, in this study, the researcher uses the theory of planned behaviour, TPB (Ajzen, 1991) as the landscape in understanding the influence of subjective norm, customers' attitude towards modem Halal Kopitiam and perceived behavioural control toward patronage intention at modem Halal Kopitiam. Besides, this study also developed a structural model by constructing halal awareness and religion towards the patronage intention at modem Halal Kopitiam to identify whether Halal awareness and religion have significant relationship with patronage intention at Kopitiam. Consequently, a total of 340 respondents from South of Kuching participated and answered questionnaires in a cross-sectional study. Then, the data was analysed by using Factor analysis, one way anova, ANOV A, Pearson correlation and so on. Results showed that subjective norm and respondents' attitude towards Kopitiam and perceived behavioural control have positive relationship with patronage intention at Kopitiam. However, the researcher found that religion and halal awareness did 'not have significant relationship with patronage intention at Kopitiam. However, the researcher found that religion has significant relationship with Halal awareness. Absolutely, the finding of this study could provide useful insights to the future researchers andKopitiams' owners and marketers. Customers also will receive the benefits if the Kopitiams' owner take action that will satisfy the clients' needs and wants.